Práticas discursivas e BNCC-EI: sobre interfaces de ambiências e experiências numa escola de educação infantil - Souza, Daiane Lanes de (2022)
This doctoral thesis is part of the LP2 research line, entitled: Public educational policies, educational practices and their interfaces, of the Graduate Program in Education, Federal University of Santa Maria (UFSM). Its theme is the action process of the National Curricular Common Base for Early Childhood Education, in view of the discursive practices of teachers from a municipal public school in Santa Maria-RS. It presents as a research problem: How are discursive practices produced in the ambiences and experiences of an Early Childhood Education school, considering the common national curriculum base. As a general objective of the research: To analyze the production of discursive practices in the environments and experiences of an Early Childhood Education school, considering the common national curriculum base. The proposed methodology is characterized by a qualitative study, based on Formative Ambiences that are characterized as a space for dialogue/listening to teaching experiences in order to reflect and (trans)form the pedagogical action from emerging demands. For the analysis of the discursive practices of the teachers, an analysis of the French Discourse Pecheux (1995) and Orlandi (2016) will be used. The theoretical basis is based on studies by Ball (2016) with the concept of public policy action, Malaguzzi (1999, 2005), Rinaldi (2016) and Barbosa (2009) with the concept of childhood school, Trois (2015) , with the concept of childhood curriculum and Avinio (2019) with the concept of ambience. Finally, we defend the thesis that the discursive practices of the BNCC and the research subjects produce effects of senses of performativity of the EI curriculum, from the perspective of the interfaces of ambiences and experiences.